Adopsi AIGC oleh Mahasiswa Desain: Efisiensi, Etika, dan Kreativitas - Freya Enggrayni; Anita Wulansari; Tri Puspa Rinjeni (MDP Student Conference, 2026)
This study aims to understand how Artificial Intelligence Generated Content (AIGC) is adopted by design students by examining the theoretical framework used and the factors that influence the intention and behavior of its use. The study was conducted through a systematic literature review by searching scientific databases and relevant references. The results of the analysis show that models such as the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT) are most frequently used, with a focus on perceived usefulness, ease of use, and performance expectations. However, in the context of design, the adoption of AIGC is also influenced by psychological factors, such as perceptions of risk and anxiety about AI, as well as ethical issues related to originality and creative integrity. These findings indicate that the acceptance of AIGC is not only a technical issue but also involves psychological considerations and creative values in the design learning process.